Characterizing the antibody response to amustaline/glutathione pathogen‐reduced red blood cells - Karim, Christopher; Panigrahi, Anil; Pearl, Ronald G.; Sodha, Neel R.; Beaver, Thomas M.; Pelletier, J. Peter R.; Nuttall, Gregory A.; Reece, T. Brett; Erickson, Anna; Hedrick, Teresa; Liu, Kathy; Bentow, Stanley; et al. (Transfusion (Philadelphia, Pa.), 2025)
Background The clinical significance of natural and treatment‐emergent antibodies specific for amustaline/glutathione pathogen‐reduced red blood cells (PRRBCs) is not known. Study Design and Methods A Phase 3, randomized clinical trial of PRRBCs (ReCePI) compared PRRBCs with conventional RBCs in cardiac or thoracic‐aorta surgery. Subjects transfused during and for 7 days after surgery were screened for PRRBC‐specific antibodies at baseline, 28 and 75 days post‐surgery. Subjects with treatment‐emergent antibodies were assessed for evidence of hemolysis. Cryopreserved subject RBC samples were assayed by flow cytometry for circulating PRRBCs using an acridine‐specific (2S197‐2M1) monoclonal antibody, and for human IgG‐coated RBCs. RBC‐surface acridine density was quantitated using a commercial calibrated phycoerythrin (PE)‐bead panel. Results Five of 159 (3.1%) PRRBC and zero of 162 conventional RBC recipients developed treatment‐emergent PRRBC‐specific IgG, low titer antibodies detected 26–80 days post‐surgery after exposure to 1–3 PRRBC units, without clinical evidence of hemolysis. DAT and eluate were weak (w+) positive and PRRBC‐specific in one subject. A monocyte monolayer assay (MMA) was non‐reactive in the three subjects with an interpretable result. Flow cytometry demonstrated circulating PRRBCs in all five subjects expressing surface acridine concentrations at the limit of detection (approximately 150–301 PE molecules/RBC) compared with freshly transfused PRRBCs (approximately 7500 PE molecules/RBC). In some samples, loss of surface acridine expression could not be distinguished from clearance of the PRRBCs. Discussion Treatment‐emergent PRRBC‐specific antibodies with the characteristics of nonclinically significant antibodies were detected in five subjects transfused with PRRBCs. Flow cytometry demonstrated persistent circulating PRRBCs with minimal surface acridine expression. (www.ClinicalTrials.gov Identifier NCT03459287).